The Association Between Sedentary Behavior and Sarcopenia Among Adults Aged >= 65 Years in Low- and Middle-Income Countries - SOYSAL, PINAR; Smith, Lee; Tully, Mark; Jacob, Louis; Blackburn, Nicole; Adlakha, Deepti; Caserotti, Paolo; SOYSAL, PINAR; Veronese, Nicola; Lopez Sanchez, Guillermo F.; Vancampfort, Davy; Koyanagi, Ai (My University, 2020)
The present study aimed to assess the association between sedentary behavior and sarcopenia among adults aged >= 65 years. Cross-sectional data from the Study on Global Ageing and Adult Health were analyzed. Sarcopenia was defined as having low skeletal muscle mass and either a slow gait speed or a weak handgrip strength. Self-reported sedentary behavior was assessed as a continuous variable (hours per day) and also as a categorical variable (0-= 11 hours/day). Multivariable logistic regression was conducted to assess the association between sedentary behavior and sarcopenia. Analyses using the overall sample and country-wise samples were conducted. A total of 14,585 participants aged >= 65 years were included in the analysis. Their mean age was 72.6 (standard deviation, 11.5) years and 55% were females. Compared to sedentary behavior of 0-= 11 hours/day was significantly associated with 2.14 (95% CI = 1.06-4.33) times higher odds for sarcopenia. The country-wise analysis showed that overall, a one-hour increase in sedentary behavior per day was associated with 1.06 (95% CI = 1.04-1.10) times higher odds for sarcopenia, while the level of between-country heterogeneity was low (I-2 = 12.9%). Public health and healthcare practitioners may wish to target reductions in sedentary behavior to aid in the prevention of sarcopenia in older adults.
Keywords: Sedentary Behavior; Sarcopenia